Utilization of Waste Banana Peels and Corn Cobs as Substrates in Neurospora sitophila Fermentation for Production of Natural Yellow Dyes - Ramadhani, Aida Nur; Ruwaidah, Listia Aulia; Rahman, Halimah Madania; Nisa, Nadya Khoirun; Septiya, Intan; Kwartiningsih, Endang (Jurnal Rekayasa Kimia & Lingkungan, 2024)
In the current situation, biomass gasification has become a major interest in producing clean energy and green chemicals. By gasification, the biomass can be converted to synthetic gas (syngas) for many purposes. However, syngas with high tar content can cause pipeline fouling and disturb the operation of downstream equipment. To reduce tar content, a two-series wet scrubber was installed for syngas cleaning produced by palm kernel shell gasification. Firstly, the gasification is operated at a temperature range of 500 600oC and 700 800oC to determine the conditions where the lowest tar syngas is produced. After that, the wet scrubber is installed with a variety of solvents including isopropyl alcohol, water, used cooking oil, and used lubricating oil. The results show that the lowest tar syngas was produced at a temperature of 800oC with a tar yield of 0.165 g/kg biomass. Meanwhile, in the same condition, isopropyl alcohol delivers the most substantial impact on tar removal efficiency, whereas used lubricating oil results in less impact. The use of isopropyl alcohol resulted in 99.25% tar removal effectiveness while lubricating oil yielded just 50.32%.